Normative Consideration on Purchase Decision - Murtini, Sri (Manunggal Halim Jaya, 2021)
The theory of planned behavior is a development of the theory of reasoned action (Ajzen, 1991). Basically the individual behavior of every human being is influenced by individual intentions (behavior intention). Behavioral intentions are influenced by three components, namely attitude, subjective norm, and perceived behavior control (Madden et al., 1992). Attitude is a positive or negative feeling of a person's belief in a behavior. Subjective norm is an individual's emotional perception that assesses the importance of the behavior to be carried out. Perceived behavioral control is an individual's perception of obstacles in carrying out a behavior. This study uses a bibliometric literature review approach with a sample mapping literature of 15 articles regarding planned behavior theory approaches reference articles from 2020 - 2021 under Scopus indexed journal. Universally, the results of this literature study state two propositions and hypotheses (e.g., Firstly, the theoretical implication states that there is a robust theoretical correlation between the theory of Planned behavior on purchase decisions; secondly, the correlation of planned behavior theory in aspects of management (e.g., marketing, Technology, Health Management, and HRM) make a positive contribution as a grounded theory to explain antecedent variables and their correlation to other approaches)